2016
DOI: 10.15517/pensarmov.v14i1.20751
|View full text |Cite
|
Sign up to set email alerts
|

Análisis Del Autoconcepto Físico Y Sus Dimensiones en Función Del Sexo De Los Adolescentes, De Una Población Media De La Cuenca Mediterránea Española

Abstract: El estudio que se presenta evaluó los niveles de autoconcepto físico de un grupo de adolescentes de manera global, en función de sus dimensiones: apariencia física, habilidad física, fuerza, equilibrio, flexibilidad, resistencia y en función del sexo en la población de 12 a 15 años de Jaén, España. La muestra está compuesta por 296 participantes, con una edad media de 13,03 años y un rango de edad entre 12 y 15 años. Se seleccionó como instrumento de medición una adaptación del Cuestionario de Autoconcepto Fís… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
3
1
0
Order By: Relevance
“…These results are in line with those obtained in the few existing studies with the older population, both longitudinal [30,31] and transversal [32][33][34]. Based on this and previous research on PSC carried out with younger populations [32,60,65,66], we suggest that PSC throughout lifespan behaves in the shape of an inverted U, developing from infancy to the beginning of adulthood, followed by a period of stability until the age of 40-50, and then decreasing, first slowly, and sharply from the age of 70, concurring with the biological stage of the greatest loss of muscle strength, mobility and functional capacity [8,67,68].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in line with those obtained in the few existing studies with the older population, both longitudinal [30,31] and transversal [32][33][34]. Based on this and previous research on PSC carried out with younger populations [32,60,65,66], we suggest that PSC throughout lifespan behaves in the shape of an inverted U, developing from infancy to the beginning of adulthood, followed by a period of stability until the age of 40-50, and then decreasing, first slowly, and sharply from the age of 70, concurring with the biological stage of the greatest loss of muscle strength, mobility and functional capacity [8,67,68].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the PC and SC dimensions, the differences occurred between the youngest and oldest age groups. As in other previous analogous studies, no statistically significant differences were found for the AT and ST dimensions [32][33][34], which indicates that the interest in both remains constant from the point of reaching adulthood.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This research also revealed differences, although not significant, have been obtained between body satisfaction in boys and girls, presenting higher scores in boys. According to results of the present research, the previous studies by Cachón-Zagalaz et al [49] and Palomares-González et al [50] obtained results similar and concluded that boys had higher body satisfaction scores than girls. In addition to this, the study conducted by Sánchez-Miguel et al [21] found that boys who engage in higher levels of physical activity are more likely to be satisfied with their physical appearance.…”
Section: Discussionsupporting
confidence: 84%